Ecological Resilience in Regional Autonomy: An Analysis of Local Political Regimes on Sustainable Natural Resources Governance - Ayu Lestari (PT. Publikasiku Academic Solution, 2025)
This article examines the relationship between local political regimes and ecological resilience in coastal natural resource management in Indonesia. Using a multi-case qualitative research method, this study evaluates the performance of coastal management policies through interviews with BUMDs, field observations, and secondary data analysis in the form of environmental statistics. The findings suggest that stable governance and collaboration between sectors can increase adaptation capacity to coastal risks, such as rip and abrasion. Areas with high governance scores tend to have better ecological indicators, such as positive changes in mangroves and improved water quality. In contrast, regions with weak political coalitions show high fluctuations in ecological performance. The practical implications of this study are the importance of continuity of funding and coordination between regional apparatus and strengthening the role of BUMD in supporting evidence-based ecological adaptation policies. This research provides new insights into the mechanisms of strengthening coastal ecological resilience through local political and policy synergies.